Rancang Bangun Sistem Informasi Kasir Berbasis Web pada TB. Kariman Jaya - Ramadhan, Rizki; Rahaningsih, Nining; Basysyar, Fadil M (MEANS (Media Informasi Analisa dan Sistem), 2022)
TB. Kariman Jaya is a shop engaged in the sale of building materials and tools. The transaction process carried out still uses conventional methods, starting from recording in books and calculating using a calculator as well as searching for data that is a problem. Based on these problems, a Web-based Cashier Information System was designed using a Visual code application with the PHP programming language. The development method used is the Waterfall method. The purpose of this research is to produce a Web-based Cashier Information System. With the Web-based Cashier Information System, it will be easier for the cashier in terms of transactions, data collection of goods, and sales reports. The results of this study are a Web-based Cashier Information System with the functions of logging in, adding data, editing data, sales transactions and sales reports and logging out. With the Web-based Cashier Information System, it is hoped that it will facilitate data collection and sales reports on TB. Karim jaya.